Implementasi Program Keluarga Harapan (PKH) di Kalurahan Sriharjo Kabupaten Bantul - Pamungkas, Panji; Khozin, Muhammad (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2025)
Poverty is still the most pressing problem faced by Indonesia. Because poverty is the most complex problem with many aspects, this problem must be addressed immediately. The Indonesian government has innovated by developing various programs for poverty alleviation. This study aims to analyze the factors that influence the implementation of the Family Hope Program (PKH) in Sriharjo Village. This study uses a qualitative descriptive research approach in the Sriharjo Village, Imogiri District, Bantul Regency. Data were collected using observation, interview and documentation techniques. The results of the study indicate that. Limitations in understanding complex language, technical terms, and concepts of beneficiaries are less accustomed to communicating formally and in long writings. Resources from the Sriharjo Village government who have not participated in the implementation process of this PKH. Lack of PKH assistants in Sriharjo Village, where there are only 2 assistants, so the implementation process is less than optimal. The attitude of PKH assistants is committed to the implementation of this assistance program, which is monitored every month on KPM in spending their assistance. Beneficiaries are still dependent on assistance and are reluctant to leave PKH. The findings show that PKH assistants have been implemented in accordance with SOPs in accordance with the guidelines. The training received by PKH assistants can be used to improve the economy.Economic empowerment training is carried out for KPM so that they are not dependent on social assistance. KPM is also expected to be confident in graduating independently with PKH, assistants and the Srihajo Village government socialize this assistance as a stepping stone for economic improvement.